La epigrafía gala tras la publicación de RIG II.2. - Hoz, Javier de (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
Short history of Gaulish epigraphical studies and state of the art after the publication of RIG II.2, that is considered in some detail.